Enhancing the nutritional value of preserved rice straw with calcite-based minerals for cattle in volcanic eruption-affected areas - Khalil, K.; Anata, D.; Hermon, H.; Hendri, H.; Achmadi, J. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
The December 2023 Mount Marapi eruption likely disrupted the mineral balance in tethered cattle by altering soil and forage composition. This study examined (1) mineral imbalances in tethered cattle and (2) the effectiveness of calcite-based mineral supplements in preserved rice straw to correct these imbalances. Hair samples from 45 cattle farms were also analyzed for minerals such as P, K, S, Na, and Cu. Rice straw was preserved with 1.2% molasses, 0.15% urea, and one of four mineral additives: cal-cined calcite (CC), enriched calcined calcite (eCC), enriched raw calcite (eRC), or commercial premix (UM). The preserved straw was fed to bulls in a 4 × 4 Latin Square design. Hair analysis revealed phosphorus deficiency in 82.2% of samples, copper deficiency in 31.1%, and excesses of sulfur and sodium in 100% and 71.1% of samples, respectively. Enriched additives improved the straw's sensory qualities and mineral profiles, reduced fungal contamination, and preserved the palatable stem portion. Blood hematology and mineral levels remained unchanged; bulls fed eCC gained 332 g/day, equal to the 354 g/day gain with UM. In conclusion, the Mount Marapi eruption significantly disrupts the min-eral status of tethered cattle, causing critical P/Cu deficiencies and S/Na excesses. eCC proves to be an effective mineral supplement, enhancing the quality of preserved straw and cattle performance in re-gions affected by the eruption.